Iron, copper and disulfide dysregulation: molecular crossroads of metabolic cell death in melanoma progression - Li, Xinge; Gao, Yan; Xing, Zhiyao; Liu, Zichuan; Zhang, Xiangyang (Frontiers in Pharmacology, 2025)
Melanoma is a highly aggressive malignant tumor arising from melanocytes, with its incidence and mortality rates continuously rising in recent years, posing a major global public health challenge. Although traditional targeted therapies and immune checkpoint inhibitors have significantly improved survival in some patients, primary and acquired resistance remain common, creating an urgent need for new treatment strategies. In recent years, metabolic cell death, ferroptosis, cuproptosis, and disulfidptosis, has shown unique advantages in melanoma research. Ferroptosis directly kills tumor cells through iron-mediated lipid peroxidation; cuproptosis relies on copper-induced mitochondrial protein aggregation to inhibit tumor proliferation; disulfidptosis arises from disulfide stress caused by glucose deprivation. This review provides a detailed analysis on the mechanisms and metabolic competition paradoxes of these three types of metabolic cell death and integrates key metabolic nodes, such as related genes SLC7A11, GPX4, FDX1, LIPT1, and PPIC. Furthermore, we discuss innovative treatment strategies that significantly enhance therapeutic efficacy and overcome resistance, including the combination of metabolic cell death with immune cell regulation, nanoparticle delivery, and sonodynamic/photodynamic therapies. Ferroptosis, cuproptosis, and disulfidptosis each possess distinct advantages and characteristics in the context of melanoma development, metastasis, and drug resistance. Leveraging both their common and unique mechanisms offers new perspectives for improving treatment outcomes.